Use of antiretroviral therapy in households and risk of HIV acquisition in rural KwaZulu-Natal, South Africa, 2004-12: a prospective cohort study - Alain Vandormael, MS; Prof. Marie-Louise Newell, PhD; Till Bärnighausen, MD; Prof. Frank Tanser, PhD (Elsevier, 2014)
Background: Studies of HIV-serodiscordant couples in stable sexual relationships have provided convincing evidence that antiretroviral therapy can prevent the transmission of HIV. We aimed to quantify the preventive effect of a public-sector HIV treatment and care programme based in a community with poor knowledge and disclosure of HIV status, frequent migration, late marriage, and multiple partnerships. Specifically, we assessed whether an individual's hazard of HIV acquisition was associated with antiretroviral therapy coverage among household members of the opposite sex. Methods: In this prospective cohort study, we linked patients' records from a public-sector HIV treatment programme in rural KwaZulu-Natal, South Africa, with population-based HIV surveillance data collected between 2004 and 2012. We used information about coresidence to construct estimates of HIV prevalence and antiretroviral therapy coverage for each household. We then regressed the time to HIV seroconversion for 14 505 individuals, who were HIV-uninfected at baseline and individually followed up over time regarding their HIV status, on opposite-sex household antiretroviral therapy coverage, controlling for household HIV prevalence and a range of other potential confounders. Findings: 2037 individual HIV seroconversions were recorded during 54 845 person-years of follow-up. For each increase of ten percentage points in opposite-sex household antiretroviral therapy coverage, the HIV acquisition hazard was reduced by 6% (95% CI 2-9), after controlling for other factors. This effect size translates into large reductions in HIV acquisition hazards when household antiretroviral therapy coverage is substantially increased. For example, an increase of 50 percentage points in household antiretroviral therapy coverage (eg, from 20% to 70%) reduced the hazard of HIV acquisition by 26% (95% CI 9-39). Interpretation: Our findings provide further evidence that antiretroviral therapy significantly reduces the risk of onward transmission of HIV in a real-world setting in sub-Saharan Africa. Awareness that antiretroviral therapy can prevent transmission to coresident sexual partners could be a powerful motivator for HIV testing and antiretroviral treatment uptake, retention, and adherence. Funding: Wellcome Trust and National Institute of Child Health and Human Development (US National Institutes of Health).